LANGUAGE ACQUISITION OF CHILDREN WITH MENTAL DISABILITIES IN PACITAN - Reza Pandudinata; Sumarlam Sumarlam; Kundharu Saddhono (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2018)
This research is a psycholinguistic research because it discusses about language acquisition. Focus of language acquisition will be discussed is language acquisition of child with severe mental disability, namely Angga, and a child with mild mental disability, namely Rafli. The purpose of this study is to explain the language acquisition of child with severe mental disability and a child with mild mental disability. This research is a qualitative research. The data of this research is basic vocabularies of child with severe mental disability and a child with mild mental disability. This research strategy is case study. This research was conducted at SLB YKK Pacitan. In this study, observation and questionnaires were used to collect the data. The results of this study were Angga, child with severe mental disability, understands 56 basic vocabularies of 200 basic vocabularies provided, while Rafli, a child with mild mental disability, was able to understand the 170 basic vocabularies. This is reasonable because the ability of child with severe mental disability and a child with mild mental disability has been very different. The child's